Causes of road surfaces failures as a result of sewage pipes failures - Kuliczkowska, Emilia (Instal, 2020)
Criteria for determining the category of road pavement failures caused by damage of sewer pipelines were proposed. Damages of sewer pipelines that impact the occurrence of road pavement collapse are listed. Differences in the collapse of road surfaces in cohesive and non-cohesive soils were indicated. The phenomenon of groundwater infiltration into the sewer and the exfiltration of sewage from the sewer to the soil were analysed in detail. They have a significant impact on accelerating the phenomenon of collapsing road surfaces.
Keywords: sewers; defects; sinkholes; categories of failures